The Role of Tibial Plateau Angle in Canine Cruciate Ligament Rupture—A Review of the Literature - Todorović, Anastasija Z.; Macanović, Mirjana V. Lazarević; Mitrović, Marko B.; Krstić, Nikola E.; Bree, Henri J. J. van; Gielen, Ingrid M. L. V. (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Cranial cruciate ligament disease is a common pathological condition in dogs that is often presented in daily clinical practice. Different risk factors for the development of this condition include breed, sex, age, bodyweight and neuter status, as well as different biological and biomechanical mechanisms. In the literature, special attention has been paid to the role of the tibial plateau angle in damage to the cranial cruciate ligament. Although the disease was first described at the beginning of last century, and since then different surgical methods have been developed to treat it, its aetiology remains unclear. In this review, contemporary literature data related to the role of tibial plateau angle in canine cranial cruciate ligament rupture are presented.
Keywords: cranial cruciate ligament; diagnostic imaging; dog; stifle joint; tibial plateau angle